The Systems for Regulating Penalties and Security Measures and Their Application in Peruvian Criminal Law - Cerna Salazar, Daniel Ernesto (2023)
The author analyses the dogmatic and political-criminal aspects related to the legal consequences of crime, that is, the sanctions that derive from it; he also discusses the origin and evolution of the different regulatory systems of penalties and security measures, determines which is the one that our criminal system will adopt and differentiates the assumptions that each of them contains for their application in each specific situation. In the final part, it reserves a legal approach to the Casación 1048-2018-Arequipa, regarding the security measure imposed on the convicted Reynaldo Huacasi Ticona, which, by cassation of the sentence issued, varied the internment in a psychiatric center initially ordered for that of outpatient treatment.